PELAKSANAAN KEBIJAKAN VAKSINISASI COVID- 19 BAGI MASYARAKAT LANSIA DI KECAMATAN BUNUT KABUPATEN PELALAWAN TAHUN 2021 - Oktavia, Vella Viki; Harirah, Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The vaccination policy is the government’s effort to deal with the Covid-19 pandemic, especially for the elderly who are vulnerable to transmission of the Covid-19 virus. Bunut Sub-district has the least number of targets, but the coverage of Covid-19 vaccinations for the elderly in Bunut Sub-district is still below the ideal target. The focus of this study discusses the implementation of the Covid-19 vaccination policy for the elderly in the Bunut Sub-District Pelalawan District in 2021. This study uses a qualitative descriptive method with data collection techniques with interview, observation and documentation techniques.This research will describe how the implementation of the Covid-19 vaccination policy for the elderly in the Bunut Sub-District, using the Van Meter and Van Horn theories. The research results show that implementation of Covid-19 vaccination for the elderly has not been optimal. This can be seen from the 6 indicators . First, the delivery of covid-19 vaccination for the elderly is slow and has not yet reached the target. Second, resources are not sufficient, because not yet supported by completeness, lack of funds or finances and maintenance of the quality of the Covid-19 vaccine. Third, the lack of communication from the puskesmas with other organizations such as village heads and religious organizations has resulted in clow Covid-19 vaccination especially for the elderly. Fourth, attitude the tendency of the executors is still lacking, seen from the discipline of the implementing staff in reporting. The effort to provide services with ball pick-up system such as door-to-door vaccination is not optimal. Keywords: Policy Implementation, Vccination Covid-19, Elderly